2021
DOI: 10.1111/jwas.12757
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of dietary probiotics with Chinese herb polysaccharides on the growth performance, immunity, disease resistance, and intestinal microbiota of rainbow trout (Oncorhynchus mykiss)

Abstract: This study evaluated the effect of probiotics (Clostridium butyricum, Bacillus coagulans) and Chinese herb polysaccharides (Astragalus polysaccharides, APS) on growth performance, immunity, disease resistance, and intestinal microbiota of rainbow trout (Oncorhynchus mykiss). Specimens of O. mykiss (n = 360; 79.9 ± 2.2 g) were fed for 42 days with different diets containing a basal diet (control, C0), supplemented with 109 CFU/kg of C. butyricum + 109 CFU/kg of B. coagulans (E1) and 109 CFU/kg of C. butyricum +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The intestinal microflora play an important role in fish, such as participating in a variety of physiological functions including feed digestion, reduction of the invasion of pathogenic bacteria, and synthesis of the trace elements, amino acids, and vitamins ( Mente et al, 2016 ; Gao et al, 2019 ; Siddik et al, 2020 ). It is well known that various factors could alter the composition of intestinal microorganisms, such as direct-fed microorganisms or diet composition ( Fan et al, 2021 ). Therefore, it was important for this study to investigate the effect of the feed additives (with or without LAB) on intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal microflora play an important role in fish, such as participating in a variety of physiological functions including feed digestion, reduction of the invasion of pathogenic bacteria, and synthesis of the trace elements, amino acids, and vitamins ( Mente et al, 2016 ; Gao et al, 2019 ; Siddik et al, 2020 ). It is well known that various factors could alter the composition of intestinal microorganisms, such as direct-fed microorganisms or diet composition ( Fan et al, 2021 ). Therefore, it was important for this study to investigate the effect of the feed additives (with or without LAB) on intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…LAB is expected to be growth promoters and immunostimulants in aquaculture ( LeBlanc et al, 2017 ). It is well known that various factors, such as direct-fed microorganisms or diet composition, could alter the composition of intestinal microorganisms ( Fan et al, 2021 ). Therefore, it is important for this study to investigate the effect of feed additives (with or without LAB) on intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Panax notoginseng saponins are the main active components of the Panax notoginseng root. They contain a mixture of dammarane-typ saponins such as Panax notoginsenoside R1, ginsenoside Rg1, Rd, and Rb1 [ 40 ]. Sun et al (2018) [ 9 ] reported that Panax notoginseng extract promoted the growth of hybrid groupers ( Epinephelus lanceolatus ♂ × Epinephelus fuscoguttatus ♀) as well as their antioxidant capacity, mainly because the active components were influenced by the Panax notoginseng saponins [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A result demonstrated that (100 g/kg) APS combined with probiotics (10 9 CFU/kg) Clostridium butyricum and (10 9 CFU/kg) Bacillus coagulans supplemented for 42 days found to increase the specific growth rate (SGR) and reduce the feed conversion ratio (FCR) in Oncorhynchus mykiss. Furthermore, fish groups supplemented with APS and prebiotic developed disease resistance and regulates the intestinal microbiota (Fan et al, 2021). Fish O. niloticus fed with APS significantly improved the growth, Feed intake (FI), SGR and immune related functions at (1500 mg/kg) of diet concentrations (Zahran et al, 2014).…”
Section: Role Of Aps In Fish Speciesmentioning
confidence: 99%